Diagnostic accuracy of self-reported food consumption and shaking chills in predicting bacteremia in outpatients: A prospective, multicenter observational study - Takayuki Komatsu; Kenji Inoue; Yuki Someya; Hiroshi Hirano; Fumihiro Saitoh; Makoto Aoki; Akihiro Inui; Lawrence M. Tierney Jr; Kentaro Mishima; Keiko Mizuno; Hiroki Takami; Tomohisa Nomura; et al. (PLoS ONE, 2025)
Bacteremia, a critical condition that can lead to sepsis, is often diagnosed using blood cultures, which may yield false positives, leading to unnecessary treatments. Although clinical indicators, such as shaking chills and food consumption, have been identified as predictors of bacteremia, their diagnostic accuracy in outpatients, particularly when considering the timing of blood collection, remains unclear. This study aimed to assess the diagnostic accuracy of self-reported food consumption and shaking chills in detecting bacteremia, focusing on the time interval between the last meal and blood culture collection. This prospective, multicenter, observational study included outpatients aged > 16 years who could eat orally and underwent blood cultures in the emergency or general medicine department from April 2019 to March 2021. Food consumption before blood culture was self-reported using a medical questionnaire and categorized as “normal” (≥80%) or “poor” (<80%). The presence of chills was also assessed. Among 534 patients (mean age 68.3 ± 21.9 years, 51.3% men), 68 had bacteremia. The absence of poor food consumption (i.e., normal food consumption) had a negative predictive value of 91.2% (95% confidence interval, 88.8–93.6) and a negative likelihood ratio of 0.66 (0.23–1.94). Excluding the blood cultures collected between 10 pm and 8 am, these values increased to 96.2% (94.5–97.8) and 0.32 (0.12–0.89), respectively. Shaking chills had a positive likelihood ratio of 3.74 (2.75–4.73), increasing to 4.21 (3.22–5.19) after the same exclusion. Self-reported shaking chills were good positive predictors of bacteremia in outpatients, whereas self-reported normal food consumption, when accounting for the time between meals, ruled out bacteremia. These findings could help improve the early diagnosis and management of bacteremia, particularly in outpatient settings, and may contribute to the development of self-report tools for clinical decision-making.